Simulation and experimental study on PID control of a quadrotor MAV with perturbation - A. Noordin; M. A. M. Basri; Z. Mohamed (Institute of Advanced Engineering and Science, 2020)
This paper presents a proportional-integral-derivative (PID) flight controller for a quadrotor micro air vehicle (MAV). The MAV (Parrot Mambo minidrones) is small, therefore, a slight perturbation will affect its performance. Hence, for the actuated dynamics, roll (ϕ), pitch (θ), yaw (ψ), and z stabilization, a PID control scheme is proposed. Furthermore, the same controller technique is also applied for under-actuated dynamics x and y position control. The newtonian model is simulated using simulink with a normal Gaussian noise of force as external disturbances. using simulink support package for Parrot Minidrones by MATLAB and based on the simulation parameter, the algorithm is deployed using Bluetooth® Low energy connection via personal area network (PAN). A slight force by hand is applied as perturbation during hovering to investigation system performances. Finally, the simulation and experimental on this commercial MAV, Parrot Mambo minidrones shows good performance of the flight controller scheme in the presence of external disturbances.